Improving The Ability to Write Action Research Articles for Teachers Through Online-Based Training - Waruwu, Marinu; Dwikurnaningsih, Yari; Satyawati, Sophia Tri (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Teachers’ professionalism influences the quality of education. Professional teachers possess knowledge and teaching skills that impact student achievement. One form of teacher professional development is developing their action research writing skill. Action research articles can be used for their continuing professional and career development. This study aims to examine the effectiveness of conducting online training on writing action research articles and its impact on participants' knowledge and skills. The research subjects were 27 junior high school teachers. This study employed a mixed-method approach, combining quantitative data in the form of numerical and statistical analysis with qualitative data in the form of narratives or textual descriptions. The research instruments included tests and questionnaires for quantitative data collection, and interviews for qualitative data collection. Data analysis was conducted using descriptive quantitative methods and qualitative methods through data reduction, data presentation, and conclusion drawing. The results showed that online-based training effectively enhanced teachers' knowledge and skills in writing action research articles. Thus, online-based training can serve as an effective alternative for professional development by improving teachers' skills in writing action research articles. The study recommends expanding the training to involve teachers from various levels and regions, providing access to and technology facilities by policymakers, and designing broader and more complex training programs.